Evaluation of inappropriate prescribing to the hospitalized elderly patients in Al Shifa hospital, Gaza, Palestine - Massoud, Lina K.; Al Agha, Hala Z.; Taleb, Mahmoud H. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: The current study aimed to assess the prevalence of inappropriate prescribing (IP) for hospitalized elderly patients at Al Shifa Hospital, Gaza, Palestine. Methods: This study was a retrospective cross-sectional study. A total of 2385 prescribed drugs for 380 elderly inpatients in internal, cardiology, and respiratory departments were screened for IP. Four criteria were used to detect IP using chart review method; Drug-drug interactions (DDIs), drug contra-indications (CI), duplication of therapy and Beers’ criteria 2012. Results: The results showed that 44.2% of patients had at least one IP. Around 33.2% of the patients had DDIs, 19.2% had IP according to Beers’ criteria and 1.1% had drug CI. There was no duplication of therapy. A total of 323 IP instances were detected. Of them, 74% for DDIs and 24.8% for Beers’ criteria. The prevalence of overall IP was significantly influenced by age (p-value=0.024), polypharmacy (p-value<0.001), degree of morbidity (p-value<0.001), and departments (p-value=0.018). The prevalence of DDIs was influenced by polypharmacy (p-value<0.001), degree of morbidity (p-value=0.001), and departments (p-value=0.005). Finally, the prevalence of IP according to Beers’ criteria was significantly influenced by departments with the highest in the cardiology department (29.7%) (P-value=0.007). Conclusions: Although the overall IP was common, it was not far higher than that reported worldwide. The majority of IP was DDIs. Age, polypharmacy, degree of morbidity and departments influenced the occurrence of IP.